2020
DOI: 10.1182/blood-2020-140936
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Profiles of Treatment-Naïve Adult Acute Myeloid Leukemia Patientswith Neutropenic Fever during Intensive Chemotherapy

Abstract: Background : The intestinal bacterial flora of febrile neutropenic patients has been found to be significantly diverse and may play a role in clinical decisions regarding antimicrobial de-escalation with predictive complications. However, there are few reports of microbiota alteration of adult acute myeloid leukemia (AML) patients. Methods : Stool samples of each treatment-naïve AML patient were collected the day before the initiation of induction chemotherapy (pretreatment), on the first date o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The investigation by Masetti et al (2022) found a consistent decline in diversity among patients with extended fever duration during the post-HSCT timeframe 17 . Similarly, Rattanathammethee et al (2020) also noted a significant decrease in alpha-diversity during the fever neutropenic phase 59 . These findings indicate that altered gut microbial diversity may have potential implications on patient outcomes.…”
Section: Discussionmentioning
confidence: 82%
“…The investigation by Masetti et al (2022) found a consistent decline in diversity among patients with extended fever duration during the post-HSCT timeframe 17 . Similarly, Rattanathammethee et al (2020) also noted a significant decrease in alpha-diversity during the fever neutropenic phase 59 . These findings indicate that altered gut microbial diversity may have potential implications on patient outcomes.…”
Section: Discussionmentioning
confidence: 82%